The consequences of military thought on agoge children education in ancient sparta - Saleh Irfan, Abdulstar; Ali Abdullah, Mohammed Amin (Humanities Journal of University of Zakho, 2023)
The research entitled “The Consequences of Military Thought on Agoge Children Education in Ancient Sparta” sheds light on the compulsory education system of children in the city-state of ancient Sparta, known as Agoge Education, in which it was conquered all aspects of Spartan boys’ lives were covered from childhood, especially from the age of seven to thirty. They were directly under the strict supervision of the state. The education of Sparta gave Sparta a culture different from other Greek states. In order to ensure the continuity of its state, Sparta needed its descendants to have military characteristics, so for this purpose the children’s education system became the main goal, as well as discussing these very harsh and brutal methods with regard to military training It was education, physical exercise, beatings, punishment, competitive games, wrestling, limited food, and barracks life, in which Spartan education included a training program, and provided a comprehensive social system, in order to prepare the male to become a professional soldier To carry out the orders of the state, to endure hard and to win the war was the main goal to build a social character in a special military direction.